Psicologia e educação : o perfil da atuação dos psicólogos(as) nas escolas em Aracaju - Fonseca, Wilson Bispo da (2015)
This research aims to investigate and verify the performance of psychologists (as) in education in Aracaju. Considering the great importance of "school" is in our society and observing the different possibilities of performance of School and Educational Psychology assisting in all its processes and stages that make up the school, it is important to contribute to a better understanding of the reality of psychologists (as) working in Aracaju / SE school system, as well as a better understanding of the role of these professionals facing the demands existing in the education sector, offering this thematic context of the data in the municipality of Aracaju. The study is based on a qualitative approach, through a bibliographic and exploratory procedure. Interviews were conducted with six psychologists (as), and applied questionnaires twenty-six psychologists who work in the area of School and Educational Psychology found at Aracaju. The results realized that training for operations in the areas is still very basic and all professionals make complementary skills training; that professionals can encompass a variety of possibilities and issues in performance in School and Educational Psychology and showed a good and extensive knowledge of the area. We hope with this research contribute to the construction of understandings of psychology in the field of education in the municipality of Aracaju, mapping their practices and content, and to stimulate new discussions, new research, new possibilities and practices.